2018
DOI: 10.1002/da.22759
|View full text |Cite
|
Sign up to set email alerts
|

Risk and protective factors underlying depression and suicidal ideation in Autism Spectrum Disorder

Abstract: Background People with Autism Spectrum Disorder (ASD) are at significantly increased risk of suicidal thoughts and behavior. Given that social difficulties in ASD often lead to social isolation, which can in turn increase the risk for depression, this study examined loneliness and social support as potential risk and protective factors associated with depression and suicidal ideation. Method The sample comprised 185 people (92 females) with ASD aged 14 to 80 years who were participating in a national survey. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
129
1
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 168 publications
(144 citation statements)
references
References 58 publications
(107 reference statements)
11
129
1
3
Order By: Relevance
“…Although our baseline finding for ASD traits is consistent with previous studies that have failed to identify a relationship between ASD traits and depression [Hedley, Uljarević, & Hedley, ; Hedley, Uljarević, Wilmot, Richdale, & Dissanayake, ], or anxiety [Uljarević et al, ], it is important to note that a number of cross‐sectional studies have identified significant relationships between these factors amongst ASD [Hedley, Uljarević, Foley, et al, ; Uljarević et al, ] and non‐ASD [Lamport & Zlomke, ; Salehzadeh et al, ] populations. Findings from our study and those of others suggests the relationship between ASD traits and psychopathology is complex and likely non‐linear, and highlights the importance of longitudinal study designs to fully characterize the role of ASD trait severity in the development and maintenance of psychopathology [Tebartz van Elst, Pick, Biscaldi, Fangmeier, & Riedel, ].…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Although our baseline finding for ASD traits is consistent with previous studies that have failed to identify a relationship between ASD traits and depression [Hedley, Uljarević, & Hedley, ; Hedley, Uljarević, Wilmot, Richdale, & Dissanayake, ], or anxiety [Uljarević et al, ], it is important to note that a number of cross‐sectional studies have identified significant relationships between these factors amongst ASD [Hedley, Uljarević, Foley, et al, ; Uljarević et al, ] and non‐ASD [Lamport & Zlomke, ; Salehzadeh et al, ] populations. Findings from our study and those of others suggests the relationship between ASD traits and psychopathology is complex and likely non‐linear, and highlights the importance of longitudinal study designs to fully characterize the role of ASD trait severity in the development and maintenance of psychopathology [Tebartz van Elst, Pick, Biscaldi, Fangmeier, & Riedel, ].…”
Section: Discussionsupporting
confidence: 89%
“…However, regression results failed to identify social support as a significant predictor of positive well‐being at follow‐up when controlling for baseline (well‐being) scores. While the association between social support and well‐being in the typical population is well replicated [Turner, ; Wilhelm et al, ], and there is growing evidence that social support may be an important protective factor against poor negative mental health outcomes (e.g., depression, suicidal ideation) in people with ASD [Hedley, Uljarević, Foley, et al, ; Hedley, Uljarević, & Hedley, ; Hedley, Uljarević, Wilmot, et al, ], our results do not strongly support this interpretation in the present sample. More research into the role of social support in improving mental health and well‐being in people with ASD is therefore needed.…”
Section: Discussioncontrasting
confidence: 62%
See 3 more Smart Citations